Rapid and noninvasive quality control of anhydrous milk fat by PTR‐MS: The effect of storage time and packaging. (22nd June 2018) - Pedrotti, M.; Khomenko, I.; Cappellin, L.; Fontana, M.; Somenzi, M.; Falchero, L.; Arveda, M.; Fogliano, V.; Biasioli, F.
Abstract: In this study, proton transfer reaction‐mass spectrometry (PTR‐MS), coupled with a time‐of‐flight mass analyzer and a multipurpose automatic sampler, was evaluated as a rapid and nondestructive tool for the quality control of anhydrous milk fat. Anhydrous milk fats packed in cardboard and bag‐in‐box were compared during refrigerated shelf life at 4°C for 9 months. Anhydrous milk fat samples were taken at 120, 180, and 240 days and measured by PTR‐MS during storage at 50°C for 11 days. Univariate and multivariate data analysis were performed in order to classify samples according to the packaging type and compare aromatic profiles. Markers related to both packaging and storage duration were identified, and all stored samples were clearly distinguishable from reference fresh samples. Significant differences in some key butter aroma compounds such as 2‐pentanone, 2‐heptanone, 2/3‐methylbutanal, acetoin, and butanoic acid were observed between different types of packaging. During the refrigerated storage, differences related to packaging are more evident, while during the storage at 50°C, the fat oxidation induced by the high temperature becomes the most relevant phenomenon independently of the packaging type. These results indicate the importance of avoiding anhydrous milk fat storage at 50°C for long times during industrial production processes. All together data demonstrated the viability of PTR‐MS as a rapid and high‐sensitivity tool in agroindustry quality control program.